Decreased frequency of peripheral blood CD8+CD25+FoxP3+regulatory T cells correlates with IL-33 levels in pre-eclampsia - Jianxiu Yu; Lei Qian; Fenghui Wu; Ming Li; Wei Chen; Hongyou Wang (Taylor & Francis Group, 2017)
Objective: We aimed to investigate the role of CD8+CD25+Foxp3+regulatory T (Treg) cells in pre-eclampsia (PE). Methods: This was a cross-sectional study of 46 patients with PE and 24 normotensive women within the third trimester of gestation. We analyzed the percentages of CD8+CD25+Foxp3+Treg cells in peripheral blood using flow cytometry and the serum levels of interleukin (IL)-6, IL-17A, IL-10, TGF-β1, IL-1β, and IL-33 by Luminex 200. Results: We found that patients with PE had lower percentages of CD8+CD25+Foxp3+Treg cells than normotensive pregnant women. In addition, the percentage of CD8+CD25+Foxp3+Treg cells was positively correlated with IL-33 concentration and negatively correlated with IL-17A concentration in patients with PE. We also found that IL-33 treatment can induce proliferation of CD8+CD25+Foxp3+Treg cells in vitro. Conclusions: These findings suggest that the reduced CD8+CD25+Foxp3+Treg cells may play a role in the pathogenesis of PE. Abbreviations PE: pre-eclampsia; PBMCs: peripheral blood mononuclear cells; CTLA-4: cytotoxic T-lymphocyteantigen-4; APCs: antigen presenting cells; TGF-β: transforming growth factor-β; IL: interleukin; Treg: cells regulatory T cells; PBS: phosphate-buffered saline; Foxp3: forkhead Box protein 3; HELLPs: hemolysis, elevated liver enzyme and low platelet syndrome